Evaluation of the Shear Modulus Degradation by a Modified Hyperbolic Function for Unconventional Geomaterials - Hernán Patiño; Fausto Molina-Gómez; Rubén Ángel Galindo-Aires (Geosciences)
The characterisation of shear modulus degradation is essential for understanding the dynamic response of geomaterials. This article presents a modified hyperbolic model that evaluates the shear modulus for various angular strains and effective confining stresses. The model has been calibrated and validated using data from 108 resonant-column tests conducted on three different types of tailings from the Riotinto mines in Huelva, Spain. These tests were conducted on saturated samples that were consolidated at effective stresses of 50, 100, 150, 200, 250, and 300 kPa, accompanied by various combinations of torsional excitations to induce distinct angular strains. The results show that the hyperbolic model effectively predicts the shear modulus degradation in unconventional geomaterials, characterising the shear modulus under the testing conditions for the three types of Riotinto tailings. Additionally, the model can identify and confirm both the initial (or maximum) shear modulus and the reference angular strain as functions of the effective confining stress. The findings and model presented in this article contribute to enhancing the stability and resilience of geotechnical structures, including tailings storage facilities, that are subjected to dynamic loading, leading to safer designs and improved infrastructure performance.